Voluntary intake of cattle on range: esophageal and hand clipped forage samples compared - M.R. Rao; L.H. Harbers; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1972)
To determine the nutritional value of an animals diet, it is necessary to know the amount of each kind of feed consumed and its digestibility. A problem in range and pasture nutrition is accurate assessment of chemical and botanical composition of diets. Little detailed information on nutritive value of range and pasture forage is available.
Keywords: Cattlemen& #x27; s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Intake; Forage; Esophageal sample